1996
DOI: 10.3109/10715769609088017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiation on Red Cell Membrane and Intracellular Oxidative Defense Systems

Abstract: Ionizing radiation is currently used for prevention of transfusion associated graft versus host disease (TAGVHD). As radiation damage is associated with the production of activated oxygen species, the aim of this study was to observe the immediate effect of ionizing radiation on red cell membrane and intracellular oxidative defense systems. Neonatal and iron deficiency (IDA) cells, known for their increased sensitivity to oxidative stress, were chosen and compared with normal cells. Irradiation was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…Thio-barbituric acid reactants such as MDA, lipid peroxides and hydroperoxides are the most commonly used markers of lipid peroxidation in tissues (Carr et al, 1993;Holley and Cheeseman, 1993). MDA is known as a very important indicator for ROS-induced oxidative damage since it is the end product of either oxidative breakdown of multiple unsaturated fatty acids or the oxygenation of arachidonic acid (Katz et al, 1996). It is reported that hypercholesterolaemia increases the serum level of lipid peroxidation in rabbits and guinea pigs (Das et al, 2000) and MDA levels in rabbits (Szczeklik et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Thio-barbituric acid reactants such as MDA, lipid peroxides and hydroperoxides are the most commonly used markers of lipid peroxidation in tissues (Carr et al, 1993;Holley and Cheeseman, 1993). MDA is known as a very important indicator for ROS-induced oxidative damage since it is the end product of either oxidative breakdown of multiple unsaturated fatty acids or the oxygenation of arachidonic acid (Katz et al, 1996). It is reported that hypercholesterolaemia increases the serum level of lipid peroxidation in rabbits and guinea pigs (Das et al, 2000) and MDA levels in rabbits (Szczeklik et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Detection of lipid hydroperoxides and conjugated dienes and tribarbituric acid-reactive substances (TBARS) such as MDA, often applies to the study of lipid peroxidation reactions (4,11,19). Thus, the presence of MDA is taken as an indicator of free-radical damage through membrane lipid peroxidation (3).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that membrane phospholipids are major targets of oxidative damage, lipid peroxidation is often the first parameter analyzed for proving the involvement of free radical damage. Thus, the presence of MDA is considered as an indicator of free‐radical damage through membrane lipid peroxidation (33). Methanol extract of heat‐processed neoginseng attenuated lipid peroxidation in rats induced by ferric ion or ferric ion plus ascorbic acid (34), Vietnamese ginseng saponin has preventive effects on the psychological stress‐induced brain cell membrane damage (35) and bacoside A (triterpenoid saponin) administration improved the antioxidant status and maintained the levels of trace elements (36).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol extract of heat‐processed neoginseng attenuated lipid peroxidation in rats induced by ferric ion or ferric ion plus ascorbic acid (34), Vietnamese ginseng saponin has preventive effects on the psychological stress‐induced brain cell membrane damage (35) and bacoside A (triterpenoid saponin) administration improved the antioxidant status and maintained the levels of trace elements (36). A number of researchers have showed that irradiation increased the formation of MDA (4,5,33). According to the results of the present study, when rats were exposed to XR (5–10 Gy) of whole‐body irradiation, lipid peroxidation was found to be significantly increased in the blood with XR dose (Fig.…”
Section: Discussionmentioning
confidence: 99%